The Association between Behavioral Treatment, Medication and ADHD Severity Levels among Adolescents: A Secondary Data Analysis - Dumpratiwi, Ajeng Nova; Basileyo, Alexie; Tan, Phan Nhat; Mei, Nai-Hwa (Universitas Muhammadiyah Surakarta, 2025)
Treatment for ADHD has now developed and has many types of treatment. Each type of treatment in various literatures is claimed to have a major impact on the treatment of children with ADHD. The 6535 samples used in this study were the results of a survey from the National Survey of Children's Health (NSCH) in the United States in 2019-2020 consisting of children aged 3-17 years diagnosed with ADHD. Quantitative approach and SPSS software version 26 were used to analyze the data. Logistic regression was used to examine the crude model in this study, namely the relationship between treatment modalities and parent-rated severity of ADHD, also adjusted for confounder variables. The results of the crude model test showed that the medication group has an OR value of 0.372 lower than the behavioral treatment group related to the severity of ADHD. According to adjusted modeling model, behavioral therapy had the strongest association with low levels of ADHD severity (OR 0.163), whereas those who received both treatments had a smaller association with perceived ADHD severity (OR 0.163). Combination treatment did not provide significantly greater advantages than medication management for core ADHD symptoms, it did enhance functional and family-related outcomes, particularly in children with anxiety disorders. Each of treatment modalities has different influence on ADHD severity, and when compared combined, medication treatment has a greater effect on lowering ADHD severity.